2018
DOI: 10.1088/1367-2630/aab8ce
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed density of states in self-generated Coulomb glasses

Abstract: We investigate the structure of metastable states in self-generated Coulomb glasses. In dramatic contrast to disordered electron glasses, we find that these states lack marginal stability. Such absence of marginal stability is reflected by the suppression of the single-particle density of states into an exponentially soft gap of the form   x -

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
5
3
0
Order By: Relevance
“…There, stability arguments imply that the DOS of an interacting electron system in the presence of quenched disorder must vanish at the Fermi energy [26], due to their long-range mutual interactions. Similar physics was also reported in clean classical Coulomb liquids, where it was shown that the long-distance potentials from electrons beyond the correlation length, when taken collectively, act as a source of (self-generated) randomness [8,16,[27][28][29]. The observations presented in Fig.…”
Section: Self-generated Randomness and Short-range Correlationssupporting
confidence: 82%
See 1 more Smart Citation
“…There, stability arguments imply that the DOS of an interacting electron system in the presence of quenched disorder must vanish at the Fermi energy [26], due to their long-range mutual interactions. Similar physics was also reported in clean classical Coulomb liquids, where it was shown that the long-distance potentials from electrons beyond the correlation length, when taken collectively, act as a source of (self-generated) randomness [8,16,[27][28][29]. The observations presented in Fig.…”
Section: Self-generated Randomness and Short-range Correlationssupporting
confidence: 82%
“…Figure 2(b) shows that, prior to the pseudogap opening observed in the full electronic spectrum, a broad dip develops already in the distribution of site potentials. Interestingly, its shape at the transition is compatible with that caused by shortrange charge correlations in self-generated Coulomb glasses, P ∼ e −V/ξ |φ| (dashed line) [29]. There, the correlation hole that forms around electrons in order to minimize their mutual interactions was shown to deplete the classical DOS below the ES bound, P ES ∼ |φ| (P ES ∼ |φ| d/α−1 in the general case in d dimensions and exponent α).…”
Section: Self-generated Randomness and Short-range Correlationssupporting
confidence: 53%
“…Both types of systems are expected to feature a relatively shallow energy landscape of accessible states due to their proximity to a uniform liquid state. It is interesting to note a possibly related observation that the ensemble of metastable states in self-generated Coulomb glasses is shallow compared with more ordinary electron glasses relying on quench disorder (31).…”
mentioning
confidence: 99%
“…The CG exhibits several hallmarks of glass, which include emergence of a charge inhomogeneity [5,6], an exponential slowing down of electron dynamics [1,2], and ergodicity breaking signified by the cooling-rate dependence and aging of resistivity [2] as well as electronic crystallization from glass [5,7], all being in line with the fundamental concept of classical structural glasses [8][9][10]. Note that the emergent CG state in organics originates from a geometrical frustration in Coulomb interactions on triangular-like lattices [3,[11][12][13], where a vast number of charge patterns are degenerate similarly to in spin-frustrated systems [14], and is conceptually distinguished from widely observed electronic inhomogeneity caused by randomly located dopants [15][16][17]. Thus, the CG state serves as a novel platform for developing the physics of frustration in charge sector.…”
mentioning
confidence: 63%